Pengaruh Ease of Use dan Information Quality Terhadap Repurchase Intention Pengguna Aplikasi Grabfood Di Kota Mataram - Kusuma, Akla Triyan; Suarti, Ayu Ritha; Fitri, Elsa; Susanty, Susanty (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research aims to determine the effect of Ease of Use and Information Quality on Repurchase Intention of Grabfood application users in Mataram City. The population in this study were all Grabfood application users in Mataram City, while the sample for this study was 100 Grabfood users using purposive sampling techniques. This type of research is associative research. Data processing in this study used SPSS 25.0 for Windows, where validity tests, reliability tests, classical assumption tests, multiple linear regression tests, significance tests (t tests) and coefficient of determination (R2) were carried out. Based on the research results, it shows that: (1) Ease of Use has a positive and significant effect on Repurchase Intention (2) Information Quality has a positive and significant effect on Repurchase Intention